2007
DOI: 10.3758/bf03194127
|View full text |Cite
|
Sign up to set email alerts
|

Within- and between-nervous-system inhibition of return: Observation is as good as performance

Abstract: Inhibition of return (IOR) has been shown to occur when an individual returns to a target location (within-person IOR) and when an individual moves to a location just engaged by another individual (between-person IOR). Although within- and between-person IOR likely result from the same inhibitory mechanisms, different processes must activate these mechanisms following the performance and observation of action. Consistent with the suggestion that the mirror neuron system may be responsible for activating the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
75
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 17 publications
9
75
1
Order By: Relevance
“…This finding appears to be inconsistent with the gaze cueing literature, which reports no IOR at the SOAs typically used in this study, following centrally presented cues (Frischen, Smilek, et al, 2007;Frischen & Tipper, 2004), and therefore with an attentional cueing account of the effect. Welsh et al (2007) also found a significant correlation between within-and between-person inhibition, which underscored the potentially shared mechanism between these two behaviours.…”
Section: Social Inhibition Of Returnmentioning
confidence: 84%
See 4 more Smart Citations
“…This finding appears to be inconsistent with the gaze cueing literature, which reports no IOR at the SOAs typically used in this study, following centrally presented cues (Frischen, Smilek, et al, 2007;Frischen & Tipper, 2004), and therefore with an attentional cueing account of the effect. Welsh et al (2007) also found a significant correlation between within-and between-person inhibition, which underscored the potentially shared mechanism between these two behaviours.…”
Section: Social Inhibition Of Returnmentioning
confidence: 84%
“…The importance of controlling for low-level stimuli in the joint IOR paradigm, as demonstrated by Welsh et al (2007), was shown in two further sets of experiments. In the first, Welsh, Ray, Weeks, Dewey, and Elliott (2009) investigated social IOR in populations with autistic spectrum disorder (ASD).…”
Section: Social Inhibition Of Returnmentioning
confidence: 99%
See 3 more Smart Citations